The partial root-zone saline irrigation system and antioxidant responses in tomato plants - Alves, Rita de Cássia [UNESP]; de Medeiros, Ana Santana; Nicolau, Mayara Cristina Malvas [UNESP]; Neto, Antônio Pizolato [UNESP]; de Assis oliveira, Francisco; Lima, Leonardo Warzea; Tezotto, Tiago [UNESP]; Gratão, Priscila Lupino [UNESP] (Elsevier, 2018)
Salinity is a limiting factor that can affect plant growth and cause significant losses in agricultural productivity. This study provides an insight about the viability of partial root-zone irrigation (PRI) system with saline water supported by a biochemical approach involving antioxidant responses. Six different irrigation methods using low and high salt concentrations (S1-0.5 and S2-5.0 dS m−1) were applied, with or without PRSI, so that one side of the root-zone was submitted to saline water while the other side was low salinity water irrigated. The results revealed different responses according to the treatments and the PRSI system applied. For the treatments T1, T2 and T3, the PRSI was not applied, while T4, T5 and T6 treatments were applied with PRSI system. Lipid peroxidation, proline content, and activities of SOD, CAT, APX, GR and GSH in tomato plants subjected to PRSI system were analyzed. Plant growth was not affected by the salt concentrations; however, plants submitted to high salt concentrations showed high MDA content and Na+ accumulation when compared to the control plants. Plants submitted to treatments T4, T5 and T6 with PRSI system exhibited lower MDA compared to the control plants (T1). Proline content and activities of SOD, CAT, APX, GR and GSH content were maintained in all treatments and tissues analyzed, with only exception for APX in fruits and GSH content, in roots. The overall results showed that PRSI system could be an applicable technique for saline water supply on irrigation since plants did not show to be vulnerable to salt stress, supported by a biochemical approach involving antioxidant responses.
Keywords: Oxidative stress; Partial root-zone irrigation; Salinity; Solanum lycopersicum L